ON POLARIZATION AND IDENTIFICATION OF POROUS PIEZOCERAMICS EFFECTIVE CHARACTERISTICS - Galina D. Vernigora; Timofey G. Lupeiko; Alexander S. Skaliukh; Arkady N. Solovyev (Advanced Engineering Research)
Features of the porous ceramics polarization based on the previously developed theory are described. The numerical study of the field remanent polarization depending on the porosity percentage in ACELAN finite element package is presented. The research results are used to model the problem of determining the piezoelectric coefficients d31 and d33. The derived values go with their known experimental behavior.